Industrial Training Report: Perbadanan Perpustakaan Awam Kelantan / Nur Ain Nabihah Adnan - Adnan, Nur Ain Nabihah (Faculty of Information Management, 2018)
Firstly, the purpose of the documentation is to report the activities during an internship for the five months in Perbadanan Perpustakaan Awam Kelantan (PPAK). Besides, daily activities on Cataloguing unit, Circulation unit, Administration unit, Kelantan collection unit and Literacy movement unit. Other than that, a special project that related to society, trainee invited students from Sekolah Menengah Kebangsaan Abdul Samad (PPKI), focus on the disabled person that can make activity on that day. The purpose of a special project is to teach students to be more creative in creating a new handicraft and to makes a good relationship between students and the library and also makes them feel happy to come to a library. Lastly, a good lesson from the industrial training that can be applied in the future.